Continous Improvement Pembelajaran Agama Islam Menggunakan AI Gemini, Kahoot, dan Nicemindmap - Kusumawati Kusumawati; Ham Idris Tumenggung (LOGIC : Jurnal Ilmu Komputer dan Pendidikan, 2025)
This study employs a qualitative method by describing the findings obtained through a technical data source triangulation procedure in the form of documents. The documents were derived from accumulated data in NiceMindMap, which had previously been imported from AI Gemini after conducting searches based on the given learning materials. The research procedures were as follows: (1) administering quizzes via Kahoot.com consisting of five questions, conducted twice; (2) converting the quiz blueprints into assignments using AI Gemini; and (3) mapping conceptual understanding using NiceMindMap. The population of this study comprised all Informatics Engineering students in the odd semester of the 2025/2026 academic year, with a sample of 60 students. The results indicate that individual assignment completion was easier using the NiceMindMap application (29.31%). The AI Gemini application facilitated the analysis of Islamic Religious Education learning within the predetermined time estimates (28.09%). Kahoot.com facilitated the analysis of Islamic Religious Education learning within the predetermined time estimates (33.1%). The NiceMindMap application also facilitated the analysis of Islamic Religious Education learning within the predetermined time estimates (26.98%). However, respondents experienced difficulties in using applications for the continuous improvement of Islamic Religious Education learning (53.12%). Difficulties in using the AI Gemini application for the continuous improvement of Islamic Religious Education learning were also reported (53.12%). Another constraint encountered when using the Al-Qur’an application during the learning process was that internet connectivity was sometimes unstable, as AI Gemini and other learning applications require a strong and adequate internet connection. Respondents noted that when the internet response was slow, the applications were delayed in producing results, thereby failing to meet the predetermined time estimates.